Satisfacción laboral de los servidores públicos del gobierno autónomo descentralizado del cantón Junín - Intriago Nieto, Silvia Patricia (2019)
The purpose of the investigation was to evaluate the job satisfaction of public servants of the Decentralized Autonomous Government of the Junín canton. Directors were interviewed to have a deeper understanding of the substantive activities they perform and the resources available to the institution, which allowed designing a SWOT matrix with opportunities, threats, strengths and weaknesses. Then, through the s23 construct, a set of items was applied, which helped determine the most relevant issues, including limited infrastructure, noise pollution, few trainings, among others. From this, it was reflected in the Ishikawa diagram reflecting the causes - effects. On the other hand, for the design of improvement strategies that enhance employee satisfaction, it was necessary to use the Benchmarking tool, this mechanism helped to collect information from other institutions regarding practices that foster work commitment, achieving Obtain a platform for the design of the improvement plan.